Optimisation of Five-Link Suspension Mechanism of a Vehicle Solid Tyres - Grzyb, A.; Kowalski, M. (Engineering Transactions, 2001)
The paper presents a method of constructing the optimum kinematic characteristics on the basis of five-link suspension. In order to solve this issue, the perturbation method of analysing nonlinear algebraic equations was used. After assuming the decision variables, defining objective functions and appropriate limitations, a sampling method of optimisation was used. Calculations enabled us to obtain a correction of characteristics of wheel steering and camber angles in comparison with initial characteristics. The obtained results indicate that it is possible to apply the above method to form the optimum characteristics of multi-link suspension mechanisms.